Pengaruh Biaya Operasional Pembiayaan Operasional (BOPO), Non Performing Financing (NPF), Dan Return On Asset (ROA) Terhadap Simpanan Mudharabah Pada Bank - Nadira Aurely; Sri Fitri Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Bank is a place of public service or public financial intermediary. Where the bank must always be in the midst of society so that excessive financial circulation in society can be accommodated and distributed to people who experience a lack of money. The purpose of this research is to find out whether the Operational Costs of Operational Financing (BOPO), Non Performing Financing (NPF), and Return On Assets (ROA) affect mudharabah deposits at Bank Muamalat Medan. The research method used is quantitative, normative juridical, literature study and an in-depth look at the facts in the field. The data sample used in this study is a representative sample with a total of 59 units for examination. In addition, researchers also used the Google Scolar database using the keywords management, sharia, sharia principles, BOPO, NPF, ROA, and mudharabah deposits. The conclusion that can be drawn from this study is that the operational costs (BOPO), non-performing financing (NPF), and return on assets (ROA) variables affect mudharabah deposits at Bank Muamalat Medan.